Impact of Monetary Policy and Foreign Direct Investment Against Indonesia's Economic Growth - Faridsky Faridsky; Syarwani Canon; Boby Rantow Payu (Gorontalo State University, 2022)
This study aims to determine the impact of monetary policy and FDI on economic growth and discuss it. The monetary indicator variables used are inflation, interest rates and exchange rates. The data used in this study are secondary data in 1990-2019 sourced from data from the Central Bureau of National Statistics and the World Bank. The analysis model in this study uses Multiple Linear Regression with the Error Correction Model (ECM) analysis model. The results of the analysis show that in the long term monetary variables (inflation, interest rates and exchange rates) have a significant effect on economic growth. And in the short term FDI has a significant effect on economic growth. It is concluded that monetary variables (inflation, interest rates and exchange rates) are the main variables that affect economic growth in the long and short term.